ANALISIS HASIL KARYA KOLASE TEMA HEWAN DAN TUMBUHAN PADA SISWA KELAS IV SDN KAUMAN BLORA - Vica Alfiana; Singgih Adhi Prasetyo; Mira Azizah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the variation in the quality of students' collage works, particularly regarding tidiness, precision in adhering materials, and creativity, which have not been fully explored optimally. In fact, creativity is one of the important elements in collage activities as it allows students to express ideas, choose materials freely, combine colors, and arrange visual elements originally. Therefore, this study aims to analyze the collage works and the level of creativity of students in creating collages themed around animals and plants in the fourth grade of SDN Kauman Blora, based on creativity indicators that include fluency, flexibility, originality, and elaboration. This research employs a qualitative descriptive approach with subjects consisting of 28 fourth-grade students from SDN Kauman Blora. Data collection techniques include observation, interviews, questionnaires, and documentation. Test the validity of the data using triangulation techniques which are used to assess the credibility of the data. The research instruments are developed based on the assessment indicators of collage works and creativity indicators. The results of the study indicate that most of the fourth-grade students of SDN Kauman Blora have been able to produce collage works well, in terms of accuracy in sticking, neatness, color matching, and creativity. However, there are still some students who experience difficulties in accuracy, color selection, and the courage to create independently. Overall, this collage activity has been effective in developing art skills, fine motor skills, and creativity in elementary school students.